Malignant mesothelioma in situ - Churg, Andrew; Hwang, Harry; Tan, Larry; Qing, Gefei; Taher, Altaf; Tong, Amy; Bilawich, Ana M; Dacic, Sanja (Histopathology, 2018)
Aims The existence of malignant mesothelioma in situ (MIS) is often postulated, but there are no accepted morphological criteria for making such a diagnosis. Methods and results Here we report two cases that appear to be true MIS on the basis of in‐situ genomic analysis. In one case the patient had repeated unexplained pleural unilateral effusions. Two thoracoscopies 9 months apart revealed only visually normal pleura. Biopsies from both thoracoscopies showed only a single layer of mildly reactive mesothelial cells. However, these cells had lost BRCA1‐associated protein 1 (BAP1) and showed loss of cyclin‐dependent kinase inhibitor 2 (CDKN2A) (p16) by fluorescence in‐situ hybridisation (FISH). NF2 was not deleted by FISH but 28% of the mesothelial cells showed hyperploidy. Six months after the second biopsy the patient has persisting effusions but no evidence of pleural malignancy on imaging. The second patient presented with ascites and minimal omental thickening on imaging, but no visual evidence of tumour at laparoscopy. Omental biopsy showed a single layer of minimally atypical mesothelial cells with rare tiny foci of superficial invasion of fat. BAP1 immunostain showed loss of nuclear BAP1 in all the surface mesothelial cells and the invasive cells. There was CDKN2A deletion, but no deletion of NF2 by FISH. Conclusions These cases show that morphologically bland single‐layered surface mesothelial proliferations with molecular alterations seen previously only in invasive malignant mesotheliomas exist, and presumably represent malignant MIS. More cases are need to understand the frequency of such changes and the time–course over which invasive tumour develops.